EFEK KOMUNIKASI TAYANGAN HOROR YOUTUBE JURNALRISA TERHADAP SUBSCRIBERNYA - Selvy Maria Widuhung (Universitas Bina Sarana Informatika, 2021)
Vlogs or video blogs are becoming a trend in today's society, various types of shows can be easily watched on the Youtube channel. However, what is most interesting is the proliferation of horror content that has won a place in the hearts of Indonesians, along with the increasing production of horror films. One of the horror-themed vlogs with the most subscribers is Jurnalrisa which introduces the life of astral beings through a mediation mechanism. Uniquely, this show not only gives the audience a sensation of fear, but also educates them through the insights gained in interacting with supernatural beings, such as how powerful a prayer is, what happens in the next world when someone dies of suicide and many more. This study uses mass communication theory, which is seen from the cognitive, affective and conative or behavioral aspects to show positive effect on followers or customers after watching Jurnalrisa videos in their real life. Among them is the increased belief and understanding of a better life, realizing that we do live side by side with supernatural beings, and being more careful in living life in order to achieve happiness in the world and in the hereafter.